Efeito do zinco em parâmetros bioquímicos e fisiológicos de Pfaffia glomerata (Spreng.) Pedersen - Bernardy, Katieli (2015)
Industrial and mining activities combined with the inadequate use of fertilizers and pesticides have contributed to increase of zinc (Zn) levels in soil. Several physiological and biochemical disorders in plants are frequently associated with the increase of heavy metals levels such Zn in the soils and the Pffafia glomerata (Spreng.) Pedersen have been used as model species in studies associated about the effect of different levels of heavy metals and already was verified that the same presented intermediate to high tolerance to various metals, as well as different responses between accessions. Thus, the present study was aimed at characterizing the effects of different concentrations of Zn on physiological and biochemical parameters of P. glomerata accessions. For the first experiment were used four levels of Zn (2, 100, 200 and 300 μM) and three accessions of P. glomerata (BRA, GD and JB) to evaluate the production of dry matter, root morphology and the level of tolerance between accessions. The JB and GD accessions showed reduction in dry matter production, both in shoots as roots, as well as reduction of area, length and root volume, however the GD accession showed increase around of level of 100 μM Zn. Already the BRA accession showed smaller variations to those same variables, however, this is due to its low growth in relation to other accessions. As base in the results of dry matter production and root parameters of accessions, the same presented the following classification in relation to tolerance to Zn: GD> JB> BRA. In the second experiment were used three levels of Zn (2, 100 and 200 mg kg-1) and the two P. glomerata accessions selected in the previous experiment (GD and JB) and evaluated the production of dry matter, photosynthetic parameters and Zn accumulation to 34 and 74 days. For most parameters evaluated the plants responded positively to dose of 100 mg Zn, and the dose of 200 mg detrimental. The maximum photosynthesis, stomatal conductance and transpiration were observed for GD accession plants by the addition of 100 mg kg-1 of Zn in soil to 34 days of cultivation. The GD accession presented increase in stomatal index with the addition of 200 mg Zn, whereas the JB did not show any alteration. The increase of Zn concentration in soil resulted in an increase in the metal concentration in plant tissues. The accession GD showed increase in Zn translocation to the leaves and reduction in the Zn accumulation in roots to 74 days, while the JB presented not differences to the Zn levels tested. In the third experiment was evaluated the influence of excess zinc about the antioxidant response and production of β-ecdysone in P. glomerata plants cultivated in two different environments. Were used the same two accessions of P. glomerata (JB and GD) and three levels of zinc (2, 100 and 200 μM) for cultivation in hydroponics with evaluations to 7 and 14 days, and the same accessions submitted to three Zn levels (2, 100 and 200 mg kg-1) for the experiment in soil with evaluated to 34 and 74 days. The effects of excess Zn on P. glomerata accessions were dependent of culture system and also evaluation period. The excess of Zn in both systems growth tested caused increase in lipid peroxidation (MDA concentration) and increase of enzyme superoxide dismutase (SOD) and guaiacol peroxidase (GPX) in both P. glomerata accessions, however, in soil experiment the accessions presented higher difference between them in relation to GPX enzyme, GD having presented the highest values. The concentration of anthocyanin in leaves and β-ecdysone in roots were significantly altered after the addition of Zn in the growth substrate. JB accession showed reduction in β-ecdysone content with the addition of Zn in soil, already for the GD was observed the opposite, however under ideal conditions the JB accession showed higher β-ecdysone content. The anthocyanin concentration varied according with the cultivation system, where the plants grown in hydroponic exhibit higher changes in both evaluation periods.